Studi Agama dan Ekonomi tentang Pengaruh Agama terhadap Etos Kerja dan Kemiskinan - Fajar Khaswara; Ilim Abdul Halim (Gunung Djati Conference Series, 2022)
Religion and economic are two things that are related. In this study, the researcher aims to discuss the correlation between religion, work ethic and poverty. The research method used in this research is to use qualitative research methods with literature study. The results of this study contain a discussion of the history of the relationship between religion and economics. This study also discusses how religion influences work ethic and poverty. The conclusion of this study shows that religious doctrine plays a role in bringing out the work ethic of its adherents. In the problem of poverty, religion is often used as a tool of legitimacy that raises inequality so that it has an impact on the poverty of the lower class.